1998
DOI: 10.1128/jvi.72.4.3351-3361.1998
|View full text |Cite
|
Sign up to set email alerts
|

Role of the β-Chemokine Receptors CCR3 and CCR5 in Human Immunodeficiency Virus Type 1 Infection of Monocytes and Microglia

Abstract: Human immunodeficiency virus type 1 (HIV-1) infection in mononuclear phagocyte lineage cells (monocytes, macrophages, and microglia) is a critical component in the pathogenesis of viral infection. Viral replication in macrophages serves as a reservoir, a site of dissemination, and an instigator for neurological sequelae during HIV-1 disease. Recent studies demonstrated that chemokine receptors are necessary coreceptors for HIV-1 entry which determine viral tropism for different cell types. To investigate the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
47
0

Year Published

1998
1998
2003
2003

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(49 citation statements)
references
References 42 publications
(40 reference statements)
2
47
0
Order By: Relevance
“…In this context, it has been recently shown that adipocytes and preadipocytes display macrophage-like characteristics (5) and monocytes/macrophages do not allow efficient entry of X4 strains, although they express both CXCR4 and CD4 (18,19). Nevertheless, R5 viruses infect monocyte/macrophage lineage efficiently (20,21), which was clearly not observed with adipocytes or preadipocytes, stressing the differences between the two cell types.…”
Section: Are Adipose Cells Infected?mentioning
confidence: 99%
“…In this context, it has been recently shown that adipocytes and preadipocytes display macrophage-like characteristics (5) and monocytes/macrophages do not allow efficient entry of X4 strains, although they express both CXCR4 and CD4 (18,19). Nevertheless, R5 viruses infect monocyte/macrophage lineage efficiently (20,21), which was clearly not observed with adipocytes or preadipocytes, stressing the differences between the two cell types.…”
Section: Are Adipose Cells Infected?mentioning
confidence: 99%
“…Chemokines HIV-1 replication is suppressed in vitro by the CC chemokines, MIP-1 a , MIP-1 b and RANTES, and the CXC chemokine SDF-1 [29][30][31] when these natural ligands bind to CCR5 and CXCR4 cell surface receptors and block or down-regulate coreceptors utilized by HIV-1 [32][33][34][35]. While there has been controversy regarding the role of chemokines in vivo , the majority of clinical studies among HIV-1 infected adults suggest that increased MIP-1 a , MIP-1 b and RANTES protect against progression of HIV-1 to clinical AIDS [36][37][38][39][40].…”
Section: Macrophagementioning
confidence: 99%
“…Both CCR2 and CCR3 can be produced by neurons, microglia, leukocytes, and T cells. CCR2 can also be produced by astrocytes (Ghorpade et al 1998;Xia et al 1998;Klein et al 1999;Coughlan et al 2000;Huffnagle et al 2000;Chakravorty et al 2001;Fife et al 2001;Banisadr et al 2002). The fact that together CCR2-and CCR3-producing cells cover the whole range of CCR5-expressing cell types provides the possibility that MCP-2-CCR2/CCR3 can replace all the functions of MCP-2-CCR5 during KA-induced hippocampal injury.…”
Section: Discussionmentioning
confidence: 99%